Cardiac Irregularities and Temporal Lobe Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs, 2004)
Ictal and peri-ictal heart rate (HR) abnormalities in 20 children and adolescents with medically refractory symptomatic temporal lobe epilepsy (TLE) were investigated at the University Hospital Vienna, Austria.